2021
DOI: 10.1063/5.0039854
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational quenching of CN− in collisions with He and Ar

Abstract: Accurate quantum dynamics simulation of the photodetachment spectrum of the nitrate anion () based on an artificial neural network diabatic potential model

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 78 publications
0
3
1
Order By: Relevance
“…These findings indicate that the inclusion of the (non-observable) proton-exchange channels subtracts flux to the purely inelastic channels but end up producing the same overall energy-transfer efficiency as obtained from the purely inelastic collisional process. (iii) In contrast with our earlier findings discussing vibrational cooling of molecular negative ions in collision with He atoms, 38,39 the present results with a cation as a partner for He show that the vibrational and rotational cooling rate coefficients are several orders of magnitude larger than in the case of anionic partners over the same range of T values. Our rovibrational rate coefficients are also of the same order of magnitude as the purely rotationally inelastic rate coefficients of our earlier study (e.g., see Fig.…”
Section: Supplementary Materialscontrasting
confidence: 99%
“…These findings indicate that the inclusion of the (non-observable) proton-exchange channels subtracts flux to the purely inelastic channels but end up producing the same overall energy-transfer efficiency as obtained from the purely inelastic collisional process. (iii) In contrast with our earlier findings discussing vibrational cooling of molecular negative ions in collision with He atoms, 38,39 the present results with a cation as a partner for He show that the vibrational and rotational cooling rate coefficients are several orders of magnitude larger than in the case of anionic partners over the same range of T values. Our rovibrational rate coefficients are also of the same order of magnitude as the purely rotationally inelastic rate coefficients of our earlier study (e.g., see Fig.…”
Section: Supplementary Materialscontrasting
confidence: 99%
“…The same conclusions were also reached by our earlier calculations for the CN − anion in collisions with the same two partners. 56 Some authors 55 also suggested scaling procedures which were found to fare slightly better but which further underline the need to have the actual rate coefficients separately computed for the two systems.…”
Section: Resultsmentioning
confidence: 99%
“…Qu et al 5 report ab initio potentials for several low-lying electronic states of NO, which allow the accurate determination of its rovibrational levels. Three-dimensional atom-diatom PESs include those for CN − + Rg (Rg = He and Ar) by Mant et al 6 and for Ar + ArH + by Koner. 7 PESs for systems involving more than three atoms are more challenging.…”
Section: A Collisional Dynamics On Ab Initio Potentials In Small Systemsmentioning
confidence: 99%
“…Desrousseaux et al 8 study the rotational excitation of PN by collisions with H 2 . In addition, Mant et al 6 report vibrational quenching cross sections for CN − by He and Ar.…”
Section: Editorialmentioning
confidence: 99%